Best Answer

20x2 + 22xy + 6y2 = 20x2 + 10xy + 12xy + 6y2 = 10x(2x + y) + 6y(2x + y)

= (2x + y)(10x + 6y) = 2(2x + y)(5x + 3y)

More answers

2(2x + y)(5x + 3y)

Q: How do you factor 20x2 plus 22xy plus 6y2?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

6y2

A: 3x-2y = 1 => 3x = 1+2y B: 3x2-2y2+5 = 0 => 3x2 = 2y2-5 Square both sides in equation A: 9x2 = 1+4y+4y2 Multiply all terms by 3 in equation B: 9x2 = 6y2-15 So it follows that:- 6y2-15 = 1+4y+4y2 and 6y2-15-1-4y-4y2 = 0 Collect like terms: 2y2-4y-16 = 0 Divide all terms by 2: y2-2y-8 = 0 Factorise: (y-4)(y+2) = 0 Therefore: y = 4 or y = -2 Substitute the above y values into the linear equation to find the values of x: The points of intersection are: (3, 4) and (-1,-2)

mathematics: to combine terms that are alike

I guess your two equations are:4x - 6y = 22x + 3y = 12Since the plus (+) and equals (=) signs have been stripped from your question.If this is the case, then they are not parallel since their gradients are not the same.Without working them out exactly, it can be seen that one is positive (equation 1.) and the other is negative (equation 2.):4x - 6y = 2 ⇒ 6y = 4x - 2 ⇒ +ve gradient2x + 3y = 12 ⇒ 3y = -2x + 12 ⇒ -ve gradient

Related questions

There is no rational factorisation of 6y2 + 19y - 13 The roots are [-19 +/- sqrt(673)]/12 which are -3.74519 and 0.57852

3(2y + 3)(y + 2)

6y2+17y-14 = (2x+7)(3x-2) when factored

It is: 3y and y

It is: (6y+1)(y-5) when factored

2(3y + 1)(y - 2)

3y^2(5y + 2)

A = 3x2 + 9xy + 6y2l = 3x + 6yA = l×w∴ w = A/l∴ w = (3x2 + 9xy + 6y2) / (3x + 6y)∴ w = x + 1

6y2 + 11y - 2 = (6y - 1) (y + 2)

6y2 - 36 = 6ySubtract 6y from each side:6y2 - 6y - 36 = 0Divide each side by 6:y2 - y - 6 = 0Factor the expression on the left side:(y + 2) (y - 3) = 0The equation is a true statement if either factor is = 0.y + 2 = 0 ==> y = -2y - 3 = 0 ==> y = 3

6y2

(3x+2y)*(5x-3y) =3x*5x + 3x*(-3y) + 2y*5x + 2y*(-3y) [This is sometimes called the FOIL method - You multiply the First members of each bracket, then the Outers, Inners, Lasts] = 15x2 - 9xy + 10xy - 6y2 = 15x2 + xy - 6y2